Report on "English Language Section of Varga Tamás Days": annual meeting, 11–12 November, 2005, Budapest, Hungary - Munkácsy, Katalin (Teaching Mathematics and Computer Science, 2006)
The Department of Mathematics Education at Teacher Training Institute of Eötvös University organised the 5th English Language Section as a part of Varga Tamás Methodical Days. We discuss the activities based on the authors’ abstracts.